Role of Goghrita in Geriatrics - Anand, Rahul; Yadav, Vandana; Bhojani, Meera K (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: A major proportion of old age population if falls prey to geriatric disorders will not only decrease the quality of life of elderly but will also offer a financial burden on treatment of geriatric disorders on the country. Ghrita is best among all fats and goghrita is best among all ghrita. Goghrita due to its unctuous property, higher smoking point, feature of sanskar, components such as mono unsaturated fatty acids, poly unsaturated fatty acids, oleic acid, and docosahexaenoic acid prevents and treats geriatric disorders. Methods: Conceptual review of ancient Ayurveda texts, texts of contemporary science including pharmacology, medicine, physiology, pathology and medicine, articles, and journals. Results: Goghrita, due to its specific features, has capability to prevent and treat geriatric disorders. Goghrita prepared by traditional method is better as it contains more docosahexaenoic acid and omega 3 fatty acids. Discussion: Physiological elevation of vata dosha is found in old age. Vata regulates nervous system and alleviation of vata dosha may result in geriatric disorders, especially of neurological origin. Goghrita pacifies vata due to its unctuous property and is thus helpful in treating and preventing geriatric disorders. Conclusion: Goghrita pacifies vata due to its unctuous property and thus may prevent and treat geriatric disorders.